Generative Masking and Asymmetric Hash Learning for Large-Scale Physiological Signal Indexing in Digital Healthcare Systems - Logan D. Hansen; Ishaan Hegde; Nirk Heiley; Chetan A. Pillai (Bioinformatics Insights and Analytics, 2026)
The exponential growth of ambulatory physiological monitoring has given rise to vast repositories of electrocardiogram, photoplethysmogram, and other biosignal waveforms, placing unprecedented pressure on retrieval and indexing infrastructure in digital healthcare systems. Traditional indexing approaches struggle to preserve clinically meaningful similarity relationships at scale while maintaining low-latency query performance. This paper addresses that gap by proposing a unified system architecture that couples generative masking with asymmetric hash learning for large-scale physiological signal indexing. Generative masking, informed by statistical priors over physiological dynamics, produces compact latent representations that suppress noise while amplifying diagnostically salient morphology. These representations are then mapped into binary hash codes through an asymmetric learning scheme where the query and database sides are allowed to follow distinct encoding pathways, and self-supervised semantic excavation aligns hash distances with hidden functional similarity. We describe the end-to-end system stack spanning edge preprocessing, cloud-based hash indexing, and federated governance layers, and we analyze how the interplay between masking and hashing resolves key structural trade-offs among retrieval precision, storage efficiency, and inference latency. Beyond technical performance, the paper examines fairness implications arising from population-specific masking priors, robustness to distributional drift in wearable sensor streams, sustainability considerations connected to model compression and edge deployment, and regulatory aspects of privacy-preserving similarity search under evolving health data protection frameworks. The discussion foregrounds infrastructural design principles that can guide the integration of generative and hashing components into future digital health platforms, ensuring that large-scale physiological signal indexing remains clinically trustworthy, equitable, and operationally sustainable.